Hellfire [videorecording (DVD)] - Lowry, Richard, 1964-; Lang, Stephen, 1952-; Lundgren, Dolph, 1959-; Keitel, Harvey (Saban Films, 2026)
"A mysterious ex-Green Beret drifter (Stephen Lang) enters a small, southern border town and discovers a community forced to participate in narcotics distribution for a ruthless crime syndicate boss (Harvey Keitel). The drifter is about to change that."--Disc container.